عمليات ادارة المعرفة وتأثيرها في تحقيق الرصا لدى الزبون : دراسة ميدانية في عينة من الشركات الصناعية العاملة في محافظة نينوى - رأفت عاصي العبيدي (PROSPECTIVE RESEARCHES, 2023)
Knowledge management has received wide attention recently by decision makers in manufacturing companies because of the large role played by this administration to achieve satisfaction of the customer and its direct contribution in improving the functioning of companies and the acquisition of personnel from the experiences and skills, which enhance its competitive position in the market. Interest in knowledge management has led a lot of companies to adopt knowledge management as a strategy to achieve satisfaction for the customer and ensure growth and continuity.The most important requirements of this feature in the twenty first century atheist and twenty is to achieve high standards of quality that are achieved through special attention to knowledge management and in particular in a subject so-called (customer satisfaction), Based on the above.This research has tried to determine operation management knowledge and its impact in achieving the satisfaction of the customer (a field study in a sample of industrial companies operating in Nineveh). The research methodology required designing model, which reflects the correlations and influence between the process of knowledge management and customer's satisfaction. It also required the representation of a group of sub-hypotheses that reflect these relations based on the diagnosis of the research variables and testing the correlations and the influence of the model of the research. This research ends with a set of conclusions and recommendations.